Precision vs. tradition: evaluating alignment accuracy and functional outcomes in robotic vs. conventional total knee arthroplasty - Mukartihal, Ravikumar; Jain, Kamal; Katariya, Ameya; Zacharias, Tomin P.; N., Kartik P.; Patil, Sharan (International Journal of Research in Orthopaedics, 2025)
Background: Total knee arthroplasty (TKA) is the treatment of choice in severe osteoarthritis (OA) knee. Robot-assisted TKA (RA-TKA) promises superior precision and personalized bone resection and alignment, whereas conventional TKA (C-TKA) relies on manual alignment techniques. This randomized controlled trial compares alignment accuracy and short-term functional outcomes between the two modalities. Methods: 100 patients with bilateral knee OA were randomized to RA-TKA (n=50) or C-TKA (n=50). Postoperative mechanical alignment (hip-knee-ankle (HKA) angle) and functional outcomes (new knee society score (NKSS) and forgotten joint score (FJS)) were assessed at 6 months. Results: RA-TKA achieved significantly better alignment, with 82% of patients within±3° of the target HKA angle compared to 64% in C-TKA (p<0.01). However, functional outcomes were comparable: KSS (RA-TKA: 205.42±6.52 vs. C-TKA: 205.4±7.94, p=0.989) and FJS (RA-TKA: 88.6±4.07 vs. C-TKA: 88.92±4.16, p=0.662). Conclusions: RA-TKA offers improved alignment accuracy over C-TKA but does not confer superior short-term functional outcomes. Despite achieving more precise mechanical alignment, no significant differences in key functional scores are observed within six months postoperatively. The potential long-term benefits of this improved alignment, such as increased implant longevity or reduced wear, remain unconfirmed and warrant further investigation in studies with extended follow-up.